Pap Smear as A Cervical Cancer Screening in Women of Childbearing Age in 2020. - Merlin Margreth Maelissa; Halidah Rahawarin; Nathalie Elischeva Kailola; Vina Zakiah Latuconsina; Ninik Ma’athia Sallatalohy (Jurnal Penelitian Pendidikan IPA, 2022)
Early detection through screening programs is one of the cervical cancer prevention strategies that can help reduce cervical cancer morbidity and mortality. One method of early detection is through Pap smear examination. This study aimed to determine the profile of pap smear results at the Nusaniwe Sub-District Health Center, Ambon City. This descriptive observational study with a cross-sectional design was conducted at Amahusu Health Center, Benteng Health Center, Waihaong Health Center, and Urimessing Health Center. Pap smear examination was performed on women of childbearing age who came for treatment at the Health Center. They had no contraindications for pap smear examination and the results of the nonreactive IgM and IgG Sars-CoV2 antibody tests. From the examination results, on a total of 38 samples, the average age of the sample was 36.89, with the youngest age being 24 years old and the oldest being 46 years old. The highest age group was >35 years (55.3%), and the most age at first sexual intercourse was in the > 20-year age group (68.4%). Then, the most parity status was the multiparous group (68.4%). Generally, the sample had never undergone cervical cancer screening, both VIA examination and previous pap smear examination (60% and 92.1%, respectively). The most pap smear results were inflammation with infectious organisms as much as 42.1%, followed by inflammation (39.5%), Negative for Intraepithelial Lesion or Malignancy (10.5%), Atypical Squamous Cells of Undetermined Significance (5.3%) and Low-Grade Squamous Intraepithelial Lesion (2.6%). The most infecting organisms were bacteria (21.1%).